Skin Colour, Abdominal Fat, and Carcass Fat of Male Alabio Duck (Anas plathyrhincos Borneo) Fed Azolla Based Ration - Samudera, R; Hidayatullah, A (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2008)
This was conducted to know the effect of Azzola usage in their dietary toward skin color abdomen fat and carcass fat of male Alabio duck. The subject of this research was male Alabio duck attain the age 3 weeks as number 80 tails, with average first body weight 390,82 ± 0,63 g. The dietary contain 16% protein and 3000 kcal energy. Observation parameters including abdomen fat percentage, carcass fat, and skin color. Complete Random Design (RAL) consist of 4 treatments and 5 repeating was applied. Each treatment unit consisted of 4 tails of male Alabio duck. Set as treatment was levels of Azzola pinnata flour usage as much as 0 (A0); 7.5 (A2); 15 (A3); and 22.5% (A4). The effect of treatment towards abdomen fat (A0, A1, A2, and A3 / 1.50; 1.41; 1.23; 0.92 %), carcass fat (A0, A1, A2, and A3 / 7.99; 7.53; 5.74; 5.25 %), and skin color (A0, A1, A2, and A3 / 2.66; 3.62; 3.94; 4.20). this research showed result of that treatment influence was significantly difference (P < 0.05). Conclusion of this research, that azolla usage within dietary is able to decrease abdomen fat degree and carcass fat, reform skin color, thus, produce yellow color or un-pale. (Animal Production 10(3): 164-167 (2008) Key Words: Alabio duck, azolla, skin color, abdomen fat, carcass fat